Enhanced Product Recovery from Glycerol Fermentation into 3-Carbon Compounds in a Bioelectrochemical System Combined with In Situ Extraction - Roume, Hugo; Arends, Jan B. A.; Ameril, Camar P.; Patil, Sunil A.; Rabaey, Korneel (Frontiers in Bioengineering and Biotechnology, 2016)
Given the large amount of crude glycerol formed as a by-product in the biodiesel industries and the concomitant decrease in its overall market price, there is a need to add extra value to this biorefinery side stream. Upgrading can be achieved by new biotechnologies dealing with recovery and conversion of glycerol present in wastewaters into value-added products, aiming at a zero-waste policy and developing an economically viable process. In microbial bioelectrochemical systems (BESs), the mixed microbial community growing on the cathode can convert glycerol reductively to 1,3-propanediol (1,3-PDO). However, the product yield is rather limited in BESs compared to classic fermentation processes, and the synthesis of side-products, resulting from oxidation of glycerol, such as organic acids represents a major burden for recovery of 1,3-PDO. Here, we show that the use of an enriched mixed microbial community of glycerol degraders and in situ extraction of organic acids positively impacts 1,3-PDO yield and allows additional recovery of propionate from glycerol. We report the highest production yield achieved (0.72 mol1,3-PDO mol-1glycerol) in electricity driven 1,3-PDO biosynthesis from raw glycerol, which is very close to the 1,3-PDO yield reported thus far for a mixed microbial culture based glycerol fermentation process. We also present a combined approach for 1,3-PDO production and propionate extraction in a single three chamber reactor system, which leads to recovery of additional 3-carbon compounds in BESs. This opens up further opportunities for an economical upgrading of biodiesel refinery side or waste streams.